THE EFFECT OF WARM GINGER WATER FOOT SOAKING THERAPY ON REDUCING BLOOD PRESSURE IN PREGNANT WOMEN WITH HYPERTENSION AT ALISAH CLINIC TREISYA MEDAN CITY IN 2024 - Krisna, Putri; Syaputri, Deswizar; SARI, Husna (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
A pregnant woman is someone carrying a developing fetus from conception to birth. Hypertension, or high blood pressure, occurs when the blood vessels consistently experience elevated pressure. To help lower blood pressure in pregnant women, a non-pharmacological method involving soaking the feet in warm ginger water is used. This study, conducted at the Alisah Treisya Clinic in Medan City, employed a pre-experimental design with a one-group pretest-posttest format. The sample consisted of 15 pregnant women, selected through purposive sampling. Data analysis was performed using the Wilcoxon test. The results showed that warm ginger water foot soak therapy significantly reduced blood pressure in pregnant women with hypertension, with a p-value of 0.01 (p < 0.05), indicating a significant effect.